Survei Penerapan Aplikasi E-Paksi dalam Inventarisasi Aset dan Penilaian Kinerja Sistem Irigasi Air Merah Rimbo Recap pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Rejang Lebong - Angga Darwantono; Rezi Munizar (Journal of Engineering and Applied Technology, 2026)
This study aims to analyze the application of the E-PAKSI app in asset inventory and performance assessment of the irrigation system at the Air Merah Rimbo Recap Weir, managed by the Rejang Lebong Regency Public Works and Spatial Planning Agency. The method used was an empirical study with a descriptive survey approach through field observations, asset inventory using the E-PAKSI application, photographic documentation, GPS coordinate recording, and data validation through triangulation with actual conditions in the field. The analysis was conducted using the application’s automatic weighting system to generate an Irrigation System Performance Index and evaluate the condition of each structural component. The results show that the weir received a performance index score of 59.82%, classified as “poor,” indicating the need for maintenance and rehabilitation, particularly for the spillway gates, which exhibited the highest level of damage. The implementation of E-PAKSI has proven to improve the efficiency of asset inventory, consistency in assessment, accuracy of asset documentation, and ease in establishing data-driven priorities for operations and maintenance. This study confirms that the digitization of irrigation asset management through E-PAKSI can strengthen the effectiveness of technical decision-making and support more sustainable water resource infrastructure management at the local government level.